Caracterização e discussão da produção científica de uma instituição de ensino superior privada - Vidotti, Maikon Venicius (2016)
To analyze the scientific production of the professors of a private institution of higher education, some variables can be identifyed and discussions can be developed. To this end it is necessary to understand the professional profile of professors who work at the institution, object of study, and the Lattes platform proves to be the most effective tool to collect information about these professionals. The Lattes platform is the main scientific information system in Brazil, integrating academic curricula of public and private institutions in a single platform, allowing management of curricular information of institutions and researchers. But the platform does not perform automated compilation of data from certain groups. Thus, it was use the ScriptLattes tool, which synthesizes in simplified form potential indicators to demonstrate the relationship not just a group of researchers, but different groups of interest. In examining the Group of professors from the institution used as a case study in this work (UNI_X), can be noted interesting indicators of professional as well as academic characterization; at the same time the scientific literature produced by these professors, whether in the institution itself or in other institutions, where vast majority owned or has bond in graduate programs. Updating of curricula, as well as the correct completion of data on its platform, are proving to be an important indicator as well as the correlation between the published works and without mention of the institution in which these are employee. So we tried to raise discussions on the topic, for better understanding and the deepening about the problem. In this way, an analysis was performed of the professors of a top private institution, through some indicators and, among them, the scientific production. This analysis enabled the development of discussions on the importance of scientific production for private institutions, because it is believed that most of these teachers do not mention the institution in scientific works. In addition, some approaches have been raised through rankings and discussions of the STS field, generating reflections on the subject.